Data Pre-Processing And Feature Selection Techniques Backward Elimination For Naïve Bayes Classification On Heart Disease Detection - Julius Warih Angkasa; Edi Noersasongk; Purwanto (Al-Makki Publisher, 2023)
According to a study published in the International Journal of Cardiology titled